PENDAMPINGAN PENGEMBANGAN DESA EKOWISATA BERBASIS COMMUNITY BASED TOURISM (CBT) DI PEKON KILUAN NEGERI, TANGGAMUS, LAMPUNG - Yulianto; Dewi Ayu Hidayati; Teuku Fahmi; Ashara Putri; Laras Marvenda; Astiwi Inayah (Jurnal Abdi Insani, 2023)
The community service activity entitled "Assistance in the Development of Ecotourism Village Based on Community Based Tourism (CBT) in Kiluan Negeri Village, Kelumbayan District, Tanggamus District, Lampung" is a follow-up to previous research that has been carried out by the community service team in 2022. Reflecting on the study, a community partnership empowerment program or Pemberdayaan Kemitraan Masyarakat was carried out with funding from the DRTPM of the Indonesian Ministry of Education, Culture, Research and Technology related to the development of ecotourism villages in Kiluan Negeri Village. This community service aims to empower local communities in developing and managing ecotourism villages in Kiluan Negeri Village, covering aspects of skills, knowledge, and experience referring to the community-based tourism/CBT approach. In this community service, several methods of activities were combined, including socialization activities targeting civil servants and village institutional administrators by involving local communities. Then counseling and assistance for Kelompok Sadar Wisata or Pokdarwis administrators, to providing material/equipment assistance for Pokdarwis. The implementation of community service programs in Kiluan Negeri Village has been carried out thoroughly and received excellent support from all components of the village community. The results of the community service implementation show that there has been an increase in the knowledge and experience of local communities in managing the development of tourism villages. In this case, local communities have been equipped with skills in managing the potential of ecotourism villages in Kiluan Negeri Village referring to the CBT approach. The provision of supporting materials/tools for Pokdarwis equipment is also very beneficial in supporting the development of ecotourism villages in Kiluan Negeri. In the end, the presence of the community service team from University of Lampung brought a new understanding of the development of CBT-based ecotourism villages.